El Excentrico, 1968-11-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
November 20, 1968[20 de noviembre de 1968]. No volume or cover number. Cover has a photo of baseball player Ernesto De La Torre, with headline, "San Jose's 1968 Pitching Sensation!"